Analisis kinerja pegawai bagian administrasi RSUP Ratatotok buyat di era sebelum pandemi COVID-19, saat pandemic, dan new normal - Riliani Manitik; Starry Homenta Rampengan; Freddy W. Wagey; Aaltje Ellen Manampiring (Intisari Sains Medis, 2022)
Introduction: The success of hospitals (RS) in carrying out their functions as health service institutions is characterized by good quality hospital services. Administrative employees as non-health workers must have good performance in order to realize quality health services. This study aimed to analyze the description of employee performance in the administration section of the Ratatotok Buyat Hospital in terms of aspects of work culture and work environment in the era before the Covid-19 pandemic, during the pandemic and the new normal era.Methods: This type of research uses a qualitative descriptive method. Data collection techniques were carried out by in-depth interviews and then documented and analyzed. To obtain the validity of the data, inspection techniques were carried out through several activities, namely triangulation. Qualitative data was obtained based on the results of in-depth interviews using the Mile and Huberman data analysis modelResults: The performance of employees in the administration section shows that systems and activities related to employee work experience changes during the pandemic when there is a decrease in employee performance when compared to performance before the pandemic, in the new normal era, employee performance has increased.Conclusion: The performance of employees in the administration of Ratatotok Buyat Hospital before the Covid-19 pandemic was very good, there was a decline in performance during the pandemic, but increased again in the new normal era. Pendahuluan: Keberhasilan rumah sakit (RS) dalam menjalankan fungsinya sebagai lembaga pelayanan kesehatan ditandai dengan kualitas pelayanan rumah sakit yang baik. Pegawai administrasi sebagai tenaga non kesehatan harus memiliki kinerja yang baik agar dapat mewujudkan pelayanan kesehatan yang berkualitas. Penelitian ini bertujuan untuk menganalisis gambaran kinerja pegawai pada bagian administrasi Rumah Sakit Umum Pusat (RSUP) Ratatotok Buyat ditinjau dari aspek budaya kerja dan lingkungan kerja pada era sebelum pandemi Covid-19, saat pandemi dan era new normal.Metode: Jenis penelitian ini menggunakan metode deskriptif kualitatif. Teknik pengumpulan data dilakukan dengan wawancara mendalam kemudian didokumentasikan dan dianalisis. Untuk mendapatkan keabsahan data, dilakukan teknik pemeriksaan yaitu dengan triangulasi. Data kualitatif diperoleh berdasarkan hasil wawancara mendalam dengan menggunakan model analisis data Mile dan Huberman.Hasil: Kinerja pegawai dibagian administrasi menunjukkan bahwa saat pandemi terjadi penurunan jika dibandingkan dengan dengan kinerja sebelum pandemi, diera new normal kinerja pegawai kembali mengalami peningkatan.Kesimpulan: Kinerja pegawai di bagian administrasi RSUP Ratatotok Buyat sebelum pandemi Covid-19 sangat baik, dan terjadi penurunan kinerja saat pandemi, namun kembali mengalami peningkatan di era new normal.